Welfare spending and political conflict in Latin America, 1970–2010. (July 2018) - Justino, Patricia; Martorano, Bruno
Highlights: Welfare spending led to reductions in conflict in Latin America between 1970 and 2010. This effect was more pronounced when associated with reductions in inequality. Other forms of expenditure did not affect the incidence of political conflict. Increasing state capacity to provide social welfare programmes may improve political stability. Abstract: We study an age-old question in political economy: does government spending on welfare ensure peace? This question was at the heart of the European Welfare State model of the early 20th century, and remains relevant today in face of rising inequalities and political conflict. Yet there is limited empirical evidence about this question. We make use of a panel of 12 Latin American countries over the period 1970–2010 to show that welfare spending has led to substantial reductions in conflict across the region. This effect is more pronounced when associated with reductions in inequality and increasing social and institutional trust.